The Influence Of Digital Marketing, Product Innovation And Competency On MSME Performance In The South Tangerang Region - Kasmad, Kasmad; Mustakim, Masran; Purnama, Aan (Jurnal Manajemen Industri dan Logistik, 2024)
The research aims to determine the influence of digital marketing, product innovation and competency on the performance of MSMEs in the South Tangerang region. This research uses a quantitative type of research with a survey approach with the method used is simple random sampling, with a sample of 96 MSME actors in the South Tangerang area. The data analysis technique for this research uses PLS software version 3.0 (Partial Least Square) with the research results showing that (1) Digital Marketing has no effect on MSME performance with at statistical value of 1.151 < t table 1.660 and a P-value of 0.250 > 0.05, (2) Product innovation has no effect on MSME performance with at statistical value of 0.949 < t table 1.660 and P-value 0.343 > 0.05 (3) Competency has a positive and significant effect on MSME performance with at statistical value of 34.254 > t table 1.660 and P -value 0.000 < 0.05. These measures can contribute to the growth and sustainability of MSMEs in the South Tangerang Region.